Methodological Investigations in Agent-Based Modelling: With Applications for the Social Sciences - Silverman, Eric (Cham Springer Nature, 2018)
Agent-Based Modelling; ABM; Artificial Intelligence; AI; Computational social science; Social simulation; Population sciences
English
Keywords: Economics, finance, business & management; Biochemical engineering; Agent-Based Modelling; ABM; Artificial Intelligence; AI; Computational social science; Social simulation; Population sciences